Knowledge, attitude, and practice of psoriasis patients toward their diseases: a web-based, cross-sectional study - Jun Tian; Lei Zhang; Xiangrong Zhao; Li Yang (Frontiers in Medicine, 2024)
ObjectiveTo investigate the knowledge, attitude, and practice (KAP) of psoriasis patients toward the disease.MethodsA web-based cross-sectional study was conducted among psoriasis patients who were diagnosed at the outpatient of Shaanxi Provincial People’s Hospital in March 2023. A self-designed questionnaire was administered for data collection and KAP assessment.ResultsA total of 526 valid questionnaires were included, including 257 males (48.86%) psoriasis patients. Their mean KAP scores were 8.09 ± 3.60 (possible range: 0–12), 31.94 ± 4.61 (possible range: 10–50), and 51.92 ± 8.83 (possible range: 15–75), respectively. Pearson’s correlation analysis showed a positive correlation between knowledge and attitude (r = 0.186, p < 0.001), a positive correlation between knowledge and practice (r = 0.313, p < 0.001), and a negative correlation between attitude and practice (r = −0.181, p < 0.001). Moreover, structural equation model showed that medication (β = 2.74, 95% CI: 2.17, 3.32, p < 0.001) has significantly positive effect on knowledge. Education (β = 0.56, 95% CI: 0.31, 0.81, p < 0.001) and duration of psoriasis (β = 1.01, 95% CI: 0.54, 1.49, p < 0.001) have significantly positive effect on attitude. Knowledge (β = 1.03, 95% CI: 0.80, 1.26, p < 0.001) and medication (β = 4.59, 95% CI: 2.78, 6.40, p < 0.001) has significantly positive effect on practice, while attitude (β = −0.41, 95% CI: −0.57, −0.26, p < 0.001) and duration of psoriasis (β = −2.53, 95% CI: −3.49, −1.57, p < 0.001) exhibit significantly negative effect on practice.ConclusionPsoriasis patients have good knowledge, positive attitude, and proactive practice toward the disease. Education, medication, duration of psoriasis might have effect on their KAP.